Nanoscale reinforcement of polypropylene composites with carbon nanotubes and clay: Dispersion state, electromagnetic and nanomechanical properties. Issue 3 (10th December 2015) - Petrova, I.; Kotsilkova, R.; Ivanov, E.; Kuzhir, P.; Bychanok, D.; Kouravelou, K.; Karachalios, Th.; Soto Beobide, A.; Voyiatzis, G.; Codegoni, D.; Somaini, F.; Zanotti, L.
Abstract : In the present study, the bifiller system incorporating various amount of multiwalled carbon nanotubes (MWCNTs) and 3 wt% clay in polypropylene is investigated to obtain composites with multifunctional performance. The dispersion state of two nanofillers in the polypropylene matrix was characterized by applying TEM and Raman spectroscopy. Both composites demonstrate similar rheological behavior with a rheological percolation threshold of ϕ p1  = 1.5 wt% for the monofiller (MWCNTs) and ϕ p2  = 2 wt% for the bifiller systems (MWCNTs and 3% clay). The effect of two nanofillers on electromagnetic and nanomechanical properties was evaluated. Above rheological percolation both type composites show considerable electromagnetic shielding efficiency at small layer thickness due mostly to the addition of MWCNTs. The nanomechanical properties improvement is strongly dependent on the structure formed by MWCNTs in the polymer. The hardness and Young's modulus, measured by nanoindentation, is higher for the bifiller systems in comparison with the monofiller one above the rheological percolation threshold. This was attributed to the continuous network structure formed by interacted MWCNTs and infiltrated fine clay stacks. POLYM. ENG. SCI., 56:269–277, 2016. © 2015 Society of Plastics Engineers